(untitled) (Research, Society and Development, 2021)
The study aims to determine the epidemiological profile of rural workers living in the northwest of the state of Rio Grande do Sul and to verify their knowledge about protection and risk factors for skin cancer development. This is a descriptive, exploratory, and quantitative study, carried out with rural workers in Horizontina city. Many interviewees have some type of information and guidance on skin cancer and its prevention, however, most of them do not use protective measures such as appropriate clothes and sunscreen and, if exposed to the sun at inappropriate times. In addition, they have a family history of skin cancer, an influential factor for its development. It is noteworthy that most have a small property and the service is manual, leading them to greater exposure to other factors. It is noted that sun exposure is harmful to the population mainly due to cumulative exposure and lack of awareness of the risk of developing skin cancer. In addition, this population is still very affected by the lack of access to education, such as health promotion and prevention groups. In this sense, there is a need for guidance, strengthening the importance of skin cancer prevention.